67‐4: Shutter‐Free Full Colour Solid State Reflective Display (SRD®). Issue 1 (28th June 2021) - Triggs, Graham; Bandhu, Lokeshwar; Newell, Oliver; Pauza, Andrew; Bhaskaran, Harish; Hosseini, Peiman
Abstract : We demonstrate for the first time a simplified thin‐film optical architecture that results in a fully bistable, full‐colour, video‐capable SRD frontplane without the need for top shutters or optical filters. The expected performance of the new architecture is quantified using simulations and initial experimental results shown on non‐pixelated, continuous films.